Effect of hemostatic risk factors on the individual probability of thrombosis during pregnancy and the puerperium - Gerhardt, Andrea; Scharf, Rüdiger E.; Zotz, Rainer B. (Thrombosis and Haemostasis, 2003)
In a retrospective study of 190 women with a first history of venous thromboembolism during pregnancy and the puerperium and 190 age-matched women with at least one prior pregnancy and no history of venous thromboembolism, the individual probability of thrombosis was determined. Assuming an overall risk of 1 in 1500 pregnancies, the probability of pregnancy-related thrombosis in carriers of homozygous factor V Leiden was 1 in 80 (odds ratio 20.6, p=0.005) and among carriers of combined heterozygous factor V Leiden and heterozygous G20210A mutation in the prothrombin gene 1 in 20 (odds ratio 88, p<0.001). The probability of thrombosis per pregnancy among women with elevated levels of factor VIII:C (>172 % activity) was 1 in 385 (odds ratio 4.5, p<0.001) and among those with increased levels of von Willebrand factor antigen (>190 %) 1 in 435 (odds ratio 4.0, p=0.002), independent of elevated factor VIII:C levels. The high prevalence of combined and homozygous defects of hemostatic components (21.6%) in patients as compared with normal women (0.86%) supports the concept that venous thromboembolism is a multicausal disorder.
Keywords: Pregnancy; venous thrombosis; risk factors; pulmonary embolism